Zastosowanie funkcji dyskryminacyjnej do badania kondycji finansowej banków - Witkowska, Aleksandra; Witkowski, Marek (The use of the discriminant function for auditing the financial condition of banks, 2006)
In this paper we presenting the thesis that the discriminant function is an effective tool to audit the financial condition of banks working in a market-economy. For verification of this thesis we used this function for probing the financial conditio of the biggest banks in Poland in the year 2004. The results of the empirical research lead to the assumptions that it is possible to get an objective and synthetic evaluation of the financial condition of a bank by using the discriminant function.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (13); 2006; nr 1126, s. 103-111